Honeybee cognitive ecology in a fluctuating agricultural setting of apple and pear trees - Diaz, Paula Carolina (2013)
Honeybees’ plasticity to adjust responses according to environmental changes has been extensively studied in the laboratory but seldom along temporal variation in natural resources. Apple (Malus domesticus) and pear (Pyrus communis) trees often coexist in mixed agricultural settings offering different resources, and their blooming periods are slightly shifted. This scenario provides an opportunity to study how changing environments influence the way the honeybees perceive, learn, discriminate, and use odorresource information along successive flowering events. We found that honeybees preferred to gather pollen on pear flowers and nectar on apple. These individual preferences correlated with variations in the type of resources collected at the colony level according to changes in the floral market. Spontaneous proboscis extension response to pear and apple floral scents of bees captured at the hives located within the crops fluctuated according to changes in floral availability too. The capability of the proboscis extension response-trained honeybees to discriminate between both floral scents at the beginning or at the end of the flowering period was also found, although bees lose this ability when both flowers were fully available. These response patterns suggest that olfactory information experienced on flowers were memorized to predict reward yet susceptible of being reversed when the floral scents were no longer available in the orchard. Combining behavioral assays and field observations, we provide here an example of how honeybees process floral odor information to make decisions about resources in a fluctuating complex environment.